Experimental study of Hf-Cu-Sn ternary system at 870 K - Romaka, L.; Romaka, V.V.; Stadnyk, Yu.; Horyn, A. (Physics and Chemistry of Solid State, 2024)
Interaction of hafnium with copper and tin was studied at 870 K over the whole concentration range using X-ray diffractometry and scanning electron microscopy. At the temperature of investigation three ternary compounds are realized in the Hf-Cu-Sn system: HfCuSn (LiGaGe-type), HfCu5Sn2 (HfCu5Sn2-type), and Hf5CuSn3 (Hf5CuSn3-type). New HfCu5Sn2 ternary stannide crystallizes in the hexagonal space group P63/mmc with cell parameters a = 0.42959(7) nm, с = 1.54165(4) nm. Electrical transport properties indicated metallic type of conductivity of the all studied ternary compounds. The DFT calculations were used to evaluate chemical bonding, elastic and physical properties of the ternary phases.